To Be or Not to Be a Pathogen: Candida albicans and Celiac Disease - Renga, Giorgia; Bellet, Marina M.; Stincardini, Claudia; Pariano, Marilena; Oikonomou, Vasilis; Villella, Valeria R.; Brancorsini, Stefano; Clerici, Carlo; Romani, Luigina; Costantini, Claudio (Frontiers in Immunology, 2019)
Celiac disease (CD) is an immune-mediated disorder triggered by the ingestion of gluten and characterized by reversible small‐bowel mucosal atrophy in genetically predisposed subjects. Although the prevalence of CD has increased, many aspects of this pathology are still unrecognized. Candida albicans, a commensal of the human gastrointestinal tract, has been linked to CD for a long time based, among others, upon the observation of similarity between the fungal wall component, hyphal wall protein 1, and CD-related gliadin T-cell epitopes. We have recently demonstrated that Candida may switch from commensal to pathogen contingent upon several players, including mast cells, key sentinels of the immune system at the interface between the environment and the host, and the pleiotropic cytokine IL-9. However, other factors are likely to play a role by altering the balance between inflammation and tolerance. In this regard, tryptophan and its metabolites are increasingly being recognized in promoting mucosal homeostasis by balancing the immune response to external cues. Based on these premises, we will discuss how the output of Candida colonization in the gut is highly contextual, being determined at the intersection of many immunological (IL-9/mast cells) and metabolic (tryptophan) pathways that ultimately dictate the Candida commensalism vs pathogenicity in CD, thus paving the way for novel therapeutic opportunities in CD.